The comparison of life compatibility between trisomy 2 and trisomy 21 (Down syndrome) by bioinformatic-based databases - Şahin, Elif İlknur and Nalkıran, İhsan and Çelik Uzuner, Selcen (The European Research Journal, 2025)
Objectives: Trisomy occurs with an extra chromosome during cell division resulting in 47 chromosomes instead of 46 in the human genome. The overexpression of gene profiles is associated with abnormal phenotypes and a range of syndromes. Theoretically, trisomy can occur for each chromosome but the survival rate of individuals with trisomy 21 is much higher than other trisomies. In this paper, we discussed the life compatibility of trisomy 21 compared to an example trisomy of one of the other chromosomes (chromosome 2) with quantitative and qualitative gene profiles using bioinformatic databases. Methods: The analyses included (i) the determination of total gene numbers and classifications, (ii) numbers and functions of housekeeping genes, tissue-specific genes, and imprinted gene numbers and (iii) comparing the profiles of the proteins involved in cell survival and cell death in both chromosomes. Results: The results indicate that trisomy 2 is likely to be incompatible with life compared to trisomy 21 because both gene enrichment and function are important factors associated with the difference in survival rates. Protein-protein interaction analyses showed that the increased interaction rate in trisomy 2 leads to more complex pathological consequences due to disruptions in cellular functions, however the limited interaction network in trisomy 21 may help explain the clinical features of Down syndrome. Conclusions: Compared to trisomy 2, the life compatibility of trisomy 21 is associated with gene numbers, functions, and protein-protein interactions.